Vertical ocean heat redistribution sustaining sea-ice concentration trends in the Ross Sea - Olivier Lecomte (Nature Portfolio, 2017)
The mechanisms responsible for the overall expansion of Antarctic sea-ice in recent decades remain unclear. Here, using observations and model results, the authors show that ice-ocean feedbacks, triggered by an external perturbation, could be responsible for changes in sea-ice extent observed in the Ross Sea.